Seaweed organic compounds source of hydrocolloids and sustainable food packaging properties, application, and future direction - Ali, Muhammad Qasim; Mohd Akmal, Azhar; Mimi Sakinah, Abdul Munaim; Nur Fathin, Ruslan; Alsubhi, Luay M.; Noormazlinah, Ahmad; Noman, Abeer Essam (Springer Nature, 2024)
Seaweed has different biologically active macromolecules, including polyphenols, fiber, proteins, and polysaccharides. Recent developments in seaweed bioactive compounds improved food packaging quality and functional properties and increased food production innovations and sustainability. Seaweed compounds are a good source of gelling, thickening, and emulsifying agents in food industrial products. Further Green Extraction methods are used for the extraction of bioactive compounds, these methods are environment friendly, with less time and high-yield production. Seaweeds incorporate antioxidants that reduce lipid oxidation, thus enhancing food's durability and nutritional value and reducing free radicals' occurrence and retard the growth of bacteria. Seaweed has increased its potential for antimicrobial packaging solutions. The manuscript explores the perspective for advancing seaweed-based films, involving property improvements, increased shelf life, and production scalability. Seaweed-based films offer sustainable packaging for fresh produce, seafood, bakeries, and confectionery products. Seaweed-derived bioactive compounds enhance the quality and safety of packaged food products and seaweed polysaccharides in food packaging are their biodegradability and environmental friendliness.